Delivery of toll-like receptor agonists by complement C3-targeted liposomes activates immune cells and reduces tumour growth. (9th August 2021) - Francian, Alexandra; Widmer, Ashley; Olsson, Troy; Ramirez, Marisabel; Heald, Darion; Rasic, Keaton; Adams, Luke; Martinson, Holly; Kullberg, Max
Abstract: Activation of antigen presenting cells (APCs) is necessary for immune recognition and elimination of cancer. Our lab has developed a liposome nanoparticle that binds to complement C3 proteins present in serum. These C3-liposomes are specifically internalised by APCs and other myeloid cells, which express complement C3-binding receptors. Known immune stimulating compounds, toll-like receptor (TLR) agonists, were encapsulated within the C3-liposomes, including monophosphoryl lipid A (MPLA), R848, and CpG 1826, specific for TLR4, TLR7/8, and TLR9 respectively. When recognised by their respective TLRs within the myeloid cells, these compounds trigger signal cascades that ultimately lead to increased expression of inflammatory cytokines and activation markers (CD80, CD83, CD86 and CD40). RT-PCR analysis of murine bone marrow cells treated with C3-liposomes revealed a significant increase in gene expression of pro-inflammatory cytokines and factors (IL-1β, IL-6, IL-12, TNF-α, IRF7, and IP-10). Furthermore, treatment of 4T1 tumour-bearing mice with C3-liposomes containing TLR agonists resulted in reduced tumour growth, compared to PBS treated mice. Collectively, these results demonstrate that C3-liposome delivery of TLR agonists activates APCs and induces tumour-specific adaptive immune responses, leading to reduced tumour growth in a breast cancer model.